If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 6 = 3x + 4 Reorder the terms: 6 + 9x = 3x + 4 Reorder the terms: 6 + 9x = 4 + 3x Solving 6 + 9x = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + 9x + -3x = 4 + 3x + -3x Combine like terms: 9x + -3x = 6x 6 + 6x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + 6x = 4 + 0 6 + 6x = 4 Add '-6' to each side of the equation. 6 + -6 + 6x = 4 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 4 + -6 6x = 4 + -6 Combine like terms: 4 + -6 = -2 6x = -2 Divide each side by '6'. x = -0.3333333333 Simplifying x = -0.3333333333
| 19-19=14-9x-[375+10x] | | 2x+3g=21 | | 3(4k+5)-19k+9+2= | | r^2+2r-12=0 | | 2(n-4)=3n-4 | | .06(a+200)+.1a=172 | | 5+3z= | | 3.6x+.9=8.8-1.5x | | 6(2x-4)=3(-x+7)+9x | | 8x+3=10x-7 | | 92+7x+9=6+4x | | 35x^2+5x=0 | | 5x^2+7x-11=0 | | 5x^2+7x+11=0 | | 13t+t^2+36= | | 4x+7=-1(x-3) | | 4-4(x+5)=7x-16 | | 4x+7=x-(x-3) | | 0.6x+0.4(50)=0.5(x+40) | | x/2=1+x-20/5 | | 3a^2-5a-12=0 | | 28=-6(b+-1)+12 | | 4x+7=x-3 | | 4b^2+20b=0 | | 11.5+0.9p=24.1 | | 13x+12-19x=-34 | | 4(7x-2)-4(3x-4)=5(3x+2)-7 | | x+7/10=4/5+x-5/8 | | 7n+2-10n=5(n+2)-8n | | 10.1-0.4y+2.5-1.5y=22-1.9y-3.5 | | 19+6a+3a-7=11a+16-2a-4 | | 7(m-3)-3m=4(m-5)-1 |